The role of organic and inorganic UV-absorbents on photopolymerization and mechanical properties of acrylate-urethane coating. (March 2020) - Nguyen, Thien Vuong; Nguyen -Tri, Phuong; Azizi, Sohrab; Dang, Tran Chien; Hoang, Duc Minh; Hoang, Thu Ha; Nguyen, Thi Linh; Bui, Thuy Thi Le; Dang, Viet Hung; Nguyen, Ngọc Linh; Le, The Tam; Nguyen, Thi Ngoc Linh; et al.
Graphical abstract: Highlights: Tinuvin 384 decreased UV curing and mechanical properties of acrylate urethane coating. Nano R-TiO2 affected insignificantly on the photocuring but improved mechanical properties. Nano A-TiO2 and nano ZnO enhanced both the photocuring and mechanical properties. A photocuring mechanism of the coating containing UV absorbers has proposed. Abstract: In this study, the kinetic of photopolymerization reaction, mechanical properties and the morphology of UV curable acrylate urethane coating were investigated. Coatings consisting of 2 wt.% of tinuvin 384, R-TiO2, A-TiO2 and ZnO were fabricated. Loading of 2 wt.% of Tinuvin 384 organic UV absorbent was found to decrease the conversion of acrylate double bonds, gel fraction, relative hardness and abrasion resistance of the coating. R-TiO2 nanoparticles showed insignificant impact on the conversion of acrylate double bonds but improved mechanical properties of the coating. A-TiO2 and ZnO enhanced both the conversion of acrylate double bonds and mechanical properties of the coatings. A mechanism of photopolymerization reaction of UV-curable acrylate urethane coating in the presence of inorganic UV absorbents has proposed. Nanoparticles were dispersed well in a polymer matrix, with a size of about 50−200 nm.